Optimal configuration of battery energy storage systems using for rooftop residential photovoltaic to improve voltage profile of distributed network. Issue 16 (5th November 2018) - Tang, Jinrui; Cai, Defu; Yuan, Chengqing; Qiu, Yuanchao; Deng, Xiangtian; Huang, Yunhui
Abstract : Due to the power mismatches between residential load and rooftop residential photovoltaic (PV) generation, voltage profile of low‐voltage distribution system (LVDN) may exceed the allowable limit during the daytime and is well below the lower limit at night. To solve this problem, an optimal configuration of battery energy storage (BES) systems is used for rooftop residential PV to improve the voltage profile of LVDN. Firstly, typical curves of residential electric load and PV generation are analysed to demonstrate the principle of integrated voltage regulation method. Secondly, two‐stage voltage regulation strategy is proposed to minimise the installed capacity of BES. More specifically, to limit the voltage with reasonable level, the reactive power capability of PV inverter can be utilised in inner stage, and BES is used in outer stage in term of storage charging at off‐peak time and discharging at the peak time. Finally, optimal configuration model is achieved by combining the two‐stage voltage control method and the constraint condition of total reduced PV generation. Simulation results indicate that the voltage level in LVDN could be controlled in a proper range by the proposed optimal configuration scheme and the total installed capacity of BES is the minimum.